2019
DOI: 10.1016/j.ymthe.2019.05.023
|View full text |Cite
|
Sign up to set email alerts
|

PTB-AS, a Novel Natural Antisense Transcript, Promotes Glioma Progression by Improving PTBP1 mRNA Stability with SND1

Abstract: Glioma, the most common primary malignancy in the brain, has high recurrence and lethality rates, and thus, elucidation of the molecular mechanisms of this incurable disease is urgently needed. Poly-pyrimidine tract binding protein (PTBP1, also known as hnRNP I), an RNA-binding protein, has various mechanisms to promote gliomagenesis. However, the mechanisms regulating PTBP1 expression are unclear. Herein, we report a novel natural antisense noncoding RNA, PTB-AS, whose expression correlated positively with PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…This lncRNA is partially antisense to BACE1, a gene encoding the β-site amyloid precursor protein cleaving enzyme 1, which plays a crucial role in the pathophysiology of Alzheimer’s disease [ 42 ]. Interestingly, it has been shown that lncRNA BACE1-AS is markedly up-regulated in brain samples from patients with Alzheimer’s disease and promotes the stability of the BACE1 transcript [ 43 ]. The lncRNA BACE1-AS regulates the expression of its sense partner through a synergistic mechanism that includes prevention of miRNA-induced mRNA decay and translational repression.…”
Section: Lncrnas Affecting Mrna Stability Via Mirna Blockagementioning
confidence: 99%
See 1 more Smart Citation
“…This lncRNA is partially antisense to BACE1, a gene encoding the β-site amyloid precursor protein cleaving enzyme 1, which plays a crucial role in the pathophysiology of Alzheimer’s disease [ 42 ]. Interestingly, it has been shown that lncRNA BACE1-AS is markedly up-regulated in brain samples from patients with Alzheimer’s disease and promotes the stability of the BACE1 transcript [ 43 ]. The lncRNA BACE1-AS regulates the expression of its sense partner through a synergistic mechanism that includes prevention of miRNA-induced mRNA decay and translational repression.…”
Section: Lncrnas Affecting Mrna Stability Via Mirna Blockagementioning
confidence: 99%
“…The lncRNA BACE1-AS regulates the expression of its sense partner through a synergistic mechanism that includes prevention of miRNA-induced mRNA decay and translational repression. Specifically, miR-485-5p and BACE1-AS share a common binding site in the sixth exon of BACE1 mRNA transcript, and thus binding of BACE1-AS to this site avoids the interaction of miR-485-5p , hindering the translational repression and destabilization of BACE1 mRNA by miR-485-5p , and eventually elevating BACE1 levels [ 43 ].…”
Section: Lncrnas Affecting Mrna Stability Via Mirna Blockagementioning
confidence: 99%
“…We and others have previously shown the uneven organ distribution of PTBP1-or PKM-targeting miRNAs under physiological conditions, as well as their downregulation in certain cancers. 24,25,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Notably, the introduction of PTBP1-targeting miRNAs induced the switch of PKM isoforms from the cancer-dominant PKM2 to PKM1. 24,25,[40][41][42][43] Nowadays, microarray data on the distribution of miRNAs across human tissues are freely available online (https://ccbweb.cs.uni-saarl and.de/tissu eatla s/).…”
Section: Org An -S Pecifi C E Xpre Ss I On Profile S Of the Ptb P1-mentioning
confidence: 99%
“…Another representative brain-specific miRNA, MIR9-5p, promotes differentiation of neuronal cells from retinal stem cells through downregulation of PTBP1; 63 the association of MIR9-5p and PTBP1 was also reported in glioma. 45 A natural antisense transcript (PTB-AS) stabilizes the expression of PTBP1, preventing the binding of MIR9-5p to the PTBP1 3′UTR. 45 Note: Gene names are described according to the Gene Nomenclature Committee of Human Genome Organization (https://www.genen ames.org/).…”
Section: Reg Ul Ati On Of P Tb P1 By B R Ain -Or Muscle-s Pecifi C mentioning
confidence: 99%
See 1 more Smart Citation